Prevalence of impacted permanent mandibular second molars in South Indian population: A cross-sectional study - Manali Ramakrishanan Srinivasan; Saravanan Poorni; Alagarsamy Venkatesh; Babu Vasanthi (Wolters Kluwer Medknow Publications, 2016)
Aims: The aim of this study is to retrospectively determine the prevalence of impacted second molars and associated dental and radiographic findings in South Indian population. Settings and Design: Cross-sectional design. Materials and Methods: Dental records of 4976 patients depending on the selection criteria from various dental clinics in South India were retrospectively analyzed in this study. All selected radiographs and records were examined by the two authors. The angle of impacted second molars was also recorded on panoramic radiographs. Data were tabulated and analyzed. Results: The prevalence of impacted second mandibular molars was found to be 0.16%. In seven cases, the impaction was unilateral with three on the left and four on the right, and in one case, it was bilateral. The prevalence was found to be more in females than males. The angle of impaction was found to range from 19° to 80°. Conclusions: Although the prevalence of impacted second molars is low, it is crucial to diagnose early for optimal treatment.